2015
DOI: 10.1073/pnas.1414930112
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of reactive oxygen species to cerebral amyloid angiopathy, vasomotor dysfunction, and microhemorrhage in aged Tg2576 mice

Abstract: Cerebral amyloid angiopathy (CAA) is characterized by deposition of amyloid β peptide (Aβ) within walls of cerebral arteries and is an important cause of intracerebral hemorrhage, ischemic stroke, and cognitive dysfunction in elderly patients with and without Alzheimer's Disease (AD). NADPH oxidase-derived oxidative stress plays a key role in soluble Aβ-induced vessel dysfunction, but the mechanisms by which insoluble Aβ in the form of CAA causes cerebrovascular (CV) dysfunction are not clear. Here, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 73 publications
4
103
0
Order By: Relevance
“…In the present study, we found that CAA is substantially reduced, with a reduction in parenchymal Aβ deposition and without an increase in microhemorrhage. ROSs are a key contributor to CAA formation, CAA-induced vessel dysfunction, and CAA-related microhemorrhage, implying that the ROS scavenger is an important therapeutic for CAA (42). These findings suggest that Edaravone would also be a promising drug candidate for CAA.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, we found that CAA is substantially reduced, with a reduction in parenchymal Aβ deposition and without an increase in microhemorrhage. ROSs are a key contributor to CAA formation, CAA-induced vessel dysfunction, and CAA-related microhemorrhage, implying that the ROS scavenger is an important therapeutic for CAA (42). These findings suggest that Edaravone would also be a promising drug candidate for CAA.…”
Section: Discussionmentioning
confidence: 93%
“…Nox subunit is present in 5 isoforms (Nox 1-5) and is a core catalytic subunit of the enzyme (Drummond et al 2011). Nox 1, 2, and 4 isoforms are present in blood vessels of the brain (Han et al 2015; Kazama et al 2004; Miller et al 2005; Park et al 2005; Park et al 2008). Genetic inactivation of Nox2 counteracts the cerebrovascular oxidative stress and the vascular dysfunction induced by Aβ, pointing to NADPH oxidase as the source of the ROS (Park et al 2005; Park et al 2008).…”
Section: Aβ Induces An Oxidative-nitrosative Stress Associated Witmentioning
confidence: 99%
“…Importantly, these vascular abnormalities are observed in the absence of deposition of Aβ in amyloid plaques or around cerebral blood vessels (cerebral amyloid angiopathy), suggesting that soluble or oligomeric Aβ is the vasotoxic species. The cerebrovascular effects of Aβ are mediated in large part by activation of the free radical-producing enzyme NADPH oxidase through the innate immunity receptor CD36, and are reversible by pharmacological or genetic approaches to scavenge radicals or block their production (Han et al, 2015; Iadecola et al, 1999; Nicolakakis et al, 2008; Park et al, 2013; 2008). However, these neurovascular alterations become irreversible in advanced disease, due to accumulation of Aβ in cerebral blood vessels which leads to damage to endothelium, smooth muscle cells and pericytes (Park et al, 2013; 2014).…”
mentioning
confidence: 99%